Endoscopic Submucosal Dissection in the Colorectum: Feasibility in the Canadian Setting - Marietta Iacucci; Gregory Eustace; Toshio Uraoka; Yutaka Saito; Miriam Fort Gasia; Jon Love; Naohisa Yahagi (Canadian Journal of Gastroenterology)
Endoscopic submucosal dissection is a minimally invasive endoscopic technique for the removal of gastrointestinal tumours that is increasingly being used for colonic neoplasms to spare resection of colon in selected patients. Colonic endoscopic submucosal dissection is technically challenging and was initially pioneered in Japan but increasingly used in selected western centres. Its use in Canada is currently limited, and the authors review the challenges and opportunities, in addition to the unique training infrastructure required to practice the procedure under supervision. Specific tools are required to perform endoscopic submucosal dissection and meticulous attention to detail is essential. The authors provide a combined Japanese and Canadian perspective to this technique, and discuss training and performance of endoscopic submucosal dissection as well as potential indications.